The Boulevard Lefebvre Disaster: A Crisis in Construction. Issue 1 (29th October 2013) - Paskins, Jacob
Abstract : On 15 January 1964, a twelve-storey housing block collapsed while under construction on boulevard Lefebvre in Paris, killing twenty workers and injuring eighteen. Ten days later, the funeral for the dead workers became a national event. Crowds flocked to the streets of Paris and work on building sites stopped in solidarity with the victims. This landmark accident marked a significant shift in attitudes towards building site safety. Within a year of boulevard Lefebvre, the French government introduced the first major building safety laws in half a century. Accidents on building sites were frequent in France during the 1960s, resulting in 1, 000 deaths annually, but boulevard Lefebvre was a seismic moment that made visible the human cost of construction work. An accident on the scale of boulevard Lefebvre revealed anxieties about architecture, technology and urban development that transcended the single event. Based on eyewitness accounts and findings from the accident investigation, this article pieces together for the first time the events surrounding the accident and the responses to it.